2019
DOI: 10.1016/j.neuroscience.2019.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Role of NaV1.6 and NaVβ4 Sodium Channel Subunits in a Rat Model of Low Back Pain Induced by Compression of the Dorsal Root Ganglia

Abstract: Low back pain is a common cause of chronic pain and disability. It is modeled in rodents by chronically compressing the lumbar dorsal root ganglia (DRG) with small metal rods, resulting in ipsilateral mechanical and cold hypersensitivity, and hyperexcitability of sensory neurons. Sodium channels are implicated in this hyperexcitability, but the responsible isoforms are unknown. In this study, we used siRNA-mediated knockdown of the pore-forming Na V 1.6 and regulatory Na V β4 sodium channel isoforms that have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 62 publications
3
16
0
Order By: Relevance
“…In the present study, we used the CCD model induced by inserting a stainless steel rod between vertebrae holes (L4 and/or L5) which has been proven to be a typical model that mimics the clinical etiology and various symptoms of low back pain 3 . In line with previous studies, we identi ed four different pain behaviors in the ipsilateral hindpaw of CCD rats, including mechanical hyperalgesia, thermal hyperalgesia, mechanical allodynia and cold allodynia [22,29], which occurred as early as 1 day after surgery and maintained at least for 14 days.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…In the present study, we used the CCD model induced by inserting a stainless steel rod between vertebrae holes (L4 and/or L5) which has been proven to be a typical model that mimics the clinical etiology and various symptoms of low back pain 3 . In line with previous studies, we identi ed four different pain behaviors in the ipsilateral hindpaw of CCD rats, including mechanical hyperalgesia, thermal hyperalgesia, mechanical allodynia and cold allodynia [22,29], which occurred as early as 1 day after surgery and maintained at least for 14 days.…”
Section: Discussionsupporting
confidence: 68%
“…As shown in the Fig.2A and Fig.2B, intraganglionar CXCR4 siRNA microinjection remarkably reduced CXCR4 expression in compressed DRG comparing with scrambled siRNA injection group. Previous studies have shown that CCD induces obvious mechanical and thermal pain sensitivity in the ipsilateral hindpaw as measured by the von Frey test and thermal stimuli, mechanical allodynia as measured by the paw withdrawal responses to a light cotton wisp stroking and cold allodynia as measured by increased withdrawal to acetone stimuli [22]. These multiple pain behaviors were also occurred as early as 1 day post CCD and maintained at least for 14 days (Fig.2).…”
Section: Knocking Down the Up-regulation Of Cxcr4 In The Compressed Dmentioning
confidence: 69%
See 3 more Smart Citations